Trio exome sequencing is highly relevant in prenatal diagnostics. (27th December 2021) - Gabriel, Heinz; Korinth, Dirk; Ritthaler, Martin; Schulte, Björn; Battke, Florian; von Kaisenberg, Constantin; Wüstemann, Max; Schulze, Bernt; Friedrich‐Freksa, Almuth; Pfeiffer, Lutz; Entezami, Michael; Schröer, Andreas; et al.
Abstract: Objective: About 3% of newborns show malformations, with about 20% of the affected having genetic causes. Clarification of genetic diseases in postnatal diagnostics was significantly improved with high‐throughput sequencing, in particular through whole exome sequencing covering all protein‐coding regions. Here, we aim to extend the use of this technology to prenatal diagnostics. Method: Between 07/2018 and 10/2020, 500 pregnancies with fetal ultrasound abnormalities were analyzed after genetic counseling as part of prenatal diagnostics using WES of the fetus and parents. Results: Molecular genetic findings could explain ultrasound abnormalities in 38% of affected fetuses. In 47% of these, disease‐causing de novo variants were found. Pathogenic variants in genes with autosomal recessive or X‐linked inheritance were detected in more than one‐third (70/189 = 37%). The latter are associated with increased probability of recurrence, making their detection important for further pregnancies. Average time from sample receipt to report was 12 days in the recent cases. Conclusion: Trio exome sequencing is a useful addition to prenatal diagnostics due to its high diagnostic yield and short processing time (comparable to chromosome analysis). It covers a wide spectrum of genetic changes. Comprehensive interdisciplinary counseling before and after diagnostics is indispensable. Key points: What's already known about this topic? It is known that about 20% of malformations in newborns can be associated with genetic causes. Whole‐exome sequencing, and especially trio exome sequencing, is an established and successful method in postnatal genetic diagnostics. Diagnostic yield for trio exome sequencing is around 37%. What does this study add? We show that trio exome sequencing is a fast and comprehensive method in prenatal diagnostics with diagnostic yield similar to that of postnatal trio exome sequencing. We provide case solution rates for different phenotypic observations from 19% for abnormalities of internal organs up to 52% for skeletal malformations.